GE_GERICHTE P/11365/2011 vom 29. Mai 2013 - GE Cour de justice (2013)
ADMINISTRATION DES PREUVES; PREUVE ILLICITE; NATURE JURIDIQUE; ASSASSINAT; TENTATIVE(DROIT PÉNAL); AGRESSION; IN DUBIO PRO REO | CPP.147; CPP.141.2; CPP.344; CP.112; CP.22; CP.134; CPP.10.3